Question

Solve the ¥ystem by clennaton2x-y=03x-2y=-3The solution is ( . )

Systems of equations
ANSWERED
asked 2021-06-16

Solve the system by clennaton \(2x-y=0\)
\(3x-2y=-3\)
The solution is ( . )

Answers (1)

2021-06-17

The given system of equation is \(2x-y=0\)
\(3x-2y=-3\)
Multiply the equation (1) by 2 and subtract it from (2), that is, \([(2)-2x(1)]\) we get.
\((3x-2y)-2(2x-y)=-3-2\times0 \rightarrow3x-2y-2\times(-y)\)

\(=-3-0\rightarrow3x-2y-4x+2y=-3 \rightarrow3x-4x+=-3 \rightarrow3x-4x=-3\)

\(\rightarrow-x=-3 \rightarrow x=3\)
Now pluging the value of y in the equation (1) we get \(\displaystyle{2}\cdot{3}-{y}={0}\to{6}-{y}={0}\to{y}={6}\)
Hence the required solution \((x,y)=(3,6)\)

0
 
Best answer

expert advice

Have a similar question?
We can deal with it in 3 hours
...